An Analysis of the Teachers Professionalism Performance of Pancasila and Civic Education at Padang City - Giawa, Tirani; Montessori, Maria; Yusuf, Muhammad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
The teachers’ professionalism performance of Pancasila and Civic Education (PPKn) was something that needs to be analyzed at this time; this greatly determines the development of a teacher's ability in carrying out of his functional duties. Therefore, the comparison and evaluation was needed in the professional performance of an educator The aim of this article was to analyze more deeply of teachers’ professional performance of Pancasila and Civic Education (PPKn) at Padang City. This research was mixed methods with a Sequential Exploratory Design approach, namely quantitative and qualitative approaches. In the quantitative approach, the data was obtained from the results of the analysis of teacher performance questionnaires and student questionnaires, then the qualitative approach data was obtained from the analysis of interview results, documents in the form of lesson plans, observation and documentation study. Based on the findings and results of data analysis described that (1) The teachers performance of Pancasila and Civic Education PPKn at SMP Negeri 20 Padang was categorized good category, because only 33.3% of teachers have low performance, while as many 66.67% of teachers already have very good and good performance categories. (2) The factors that influence the performance of teachers in schools at SMP Negeri 20 Padang was qualification for Civics teacher education standards, the leadership factor of the school principal, the training factor, and the teacher competency factor. (3) The efforts to improve teacher performance at SMPN 20 Padang can be done through coaching, upgrading, training to improve teacher competence. Keyword: Teacher Professionalism, Teacher Performance, Civic Teachers Professionalism